Israel/Palestine and the Queer International - Schulman, Sarah, 1958- (Book collections on Project MUSE., 2012)
At once a memoir, a call to support the Boycott, Divestment and Sanctions movement, and an argument for queer solidarity across borders, this book tells the story of how novelist and activist Sarah Schulman became aware of how issues of the Israeli occupation of Palestine were tied to her own gay and lesbian politics.